Consolidating democracy, building civil society : the South African Council of Churches in post-apartheid South Africa and its policy of critical solidarity with the state - Joseph, Stacey-Leigh (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2005)
The South African Council of Churches (SACC) played an extremely crucial role during the struggle against apartheid. The role of the SACC was first and foremost to provide a voice for the voiceless. It managed, among other tasks, to actively fill the void left by movements banned by the illegitimate apartheid government. As a result of its fight against the inequalities that existed in South Africa, its work adopted a political character. In the aftermath of post-apartheid South Africa, the SACC was left with the task of redefining its role within South African society and civil society, specifically. The euphoric sentiment in the mid-1990s was in part reflected in the SACC. However, the conclusion reached by the Council in 1995 was that it would also play a role of 'critical solidarity' which essentially meant that it would not shy away from attacking the government when the need arose. Since 1994, the South African government has implemented a number of policies that do not appear to be in the immediate interest of the majority of South African citizens atld have brought church and state into conflict. This thesis attempts to tackle three issues which are pertinent to the South African situation and which shed light on state-civil society interactions. These issues are HIV I Aids, the question of odious debt and the Zimbabwe crisis. By using both primary and secondary sources, the SACC's responses to government's handling of these matters will be compared with the responses of the South African Catholic Bishops Conference in order to determine their relationships with government. The conclusion of this investigation is that the SACC has in fact managed to maintain a position of critical solidarity. It has been faced with numerous challenges with regard to maintaining the fragile boundary of alliance with government on the one hand, and becoming anti-government on the other. However, by forming alliances with other civil society actors as well as fostering a relationship with government in order to facilitate mediation this dissertation argues that the SACC has become an essential member of South Africa's vibrant civil society.
Keywords: South African Council of Churches; Church and state -- South Africa; Christianity and politics -- South Africa; Apartheid -- Religious aspects -- South Africa; AIDS (Disease) -- Government policy -- South Africa; Debts, External -- South Africa; South Africa -- Foreign relations -- Zimbabwe; South Africa -- Politics and government -- 1994